Characterising the frequency‐response of ultra‐soft polymers with the Virtual Fields Method. (18th May 2021) - Graham, Aaron; Siviour, Clive
Abstract: This paper presents a novel apparatus, combined with application of the Virtual Fields Method (VFM) for the high frequency characterisation of the mechanical response of ultra‐soft materials. The viscoelastic response is characterised under harmonic deviatoric loading at a range of frequencies using the dynamic VFM in the frequency domain. Obtaining useful high rate data on soft materials is challenging using typical test methodologies, as the low speed of sound in the material makes stress equilibrium difficult to obtain; additionally, the low stiffness results in small stresses and weak measurement signals. This novel apparatus and analysis method have been shown capable of obtaining important material characterisation data that would be impossible to access using currently existing test techniques.